ANATOMICAL VARIATIONS OF LEAVES PETIOLES IN SOME TAXA OF THE GENUS TRIFOLIUM L. (FABACEAE) IN IRAQ. - Al-dabbagh, S. T. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted on the 22 taxa of the genus Trifolium L. which grow naturally as wild plants in all geographical districts in Iraq. A comparative study of the leaf petioles was anatomically examined by paraffin method. Petiole cross-section outline shapes have divided the genus species into fourteen groups and sub-groups. According to the microscopical characteristics the cortex of petioles showed to contain layers of various tissues, the collenchyma tissue observed sub-epidermally in some species, and cortexes of the others were devoid of collenchyma. The sclerenchyma strands were noted in three patterns; above vascular bundles, above and beneath vascular bundles, and the sclerenchyma strands completely surrounded the vascular bundles in some species. Petiole cross-sections have been divided into three categories as; three vascular bundles and absent of accessory vascular bundles, three vascular bundles with one of accessory vascular bundle, three vascular bundles with two accessory vascular bundles. The comparative results confirmed that these characteristics collectively are of high taxonomic value and can contribute to separating the studied genus species, finally, based on these variations, the anatomical classification key was constructed to separate the genus taxa.